Radiobiological quantities in proton-therapy: Estimation and validation using Geant4-based Monte Carlo simulations. (February 2019) - Petringa, G.; Romano, F.; Manti, L.; Pandola, L.; Attili, A.; Cammarata, F.; Cuttone, G.; Forte, G.; Manganaro, L.; Pipek, J.; Pisciotta, P.; Russo, G.; et al.
Highlights: Monte Carlo approaches to calculate the Survival Fraction in clinical proton beam. Computational method based to coupling Geant4 and LEM-III. Computational method based to a parametrized approach. Comparison with experimental data of two cell lines acquired at LNS-INFN. Abstract: Purpose: The Geant4 Monte Carlo simulation toolkit was used to reproduce radiobiological parameters measured by irradiating three different cancerous cell lines with monochromatic and clinical proton beams. Methods: The experimental set-up adopted for irradiations was fully simulated with a dedicated open-source Geant4 application. Cells survival fractions was calculated coupling the Geant4 simulations with two analytical radiobiological models: one based on the LEM (Local Effect Model) approach and the other on a semi-empirical parameterisation. Results was evaluated and compared with experimental data. Results and conclusions: The results demonstrated the Geant4 ability to reproduce radiobiological quantities for different cell lines.